2020
DOI: 10.1136/jech-2020-215002
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and cardiovascular mortality in Rio de Janeiro, Brazil: effect modification by individual-level and neighbourhood-level factors

Abstract: BackgroundMany factors related to susceptibility or vulnerability to temperature effects on mortality have been proposed in the literature. However, there is limited evidence of effect modification by some individual-level factors such as occupation, colour/race, education level and community-level factors. We investigated the effect modification of the temperature–cardiovascular mortality relationship by individual-level and neighbourhood-level factors in the city of Rio de Janeiro, Brazil.MethodsWe used a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…A number of studies found differences between men and women in health effects and mortality from cardiovascular diseases in relation to weather conditions and other meteorological factors [49][50][51]. The strong male/female difference in depression is wellknown and is often reported in the literature [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found differences between men and women in health effects and mortality from cardiovascular diseases in relation to weather conditions and other meteorological factors [49][50][51]. The strong male/female difference in depression is wellknown and is often reported in the literature [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…In previous research conducted in Rio de Janeiro [32], we found that the cardiovascular mortality risk increased with ambient temperature, and estimates of the heat effect were greater for older people and women. In the present study, our sensitivity analyzes suggest that, beyond the temperature effect, an additional effect arises from the duration of heat sustained over several consecutive days, in line with Gasparrini and Armstrong [33].…”
Section: Discussionmentioning
confidence: 61%
“…Another Chinese study also showed that the death risk of PM 2.5 at low temperature was higher than that at medium temperature ( 27 ). Cold temperatures can lead to vasoconstriction and the release of inflammatory markers in the blood, which may increase blood pressure and vascular resistance, and finally trigger cardiovascular events ( 28 ). In comparison to previous explorations, our analysis provides details of the changing cold effect by PMs levels over lag days.…”
Section: Discussionmentioning
confidence: 99%